Factors that influence intraocular pressure changes after myopic and hyperopic LASIK and photorefractive keratectomy: a large population study - Schallhorn, Julie M; Schallhorn, Steven C; Ou, Yvonne (Ophthalmology (Rochester, Minn.), 2015)
To describe the factors that influence the measured intraocular pressure (IOP) change and to develop a predictive model after myopic and hyperopic LASIK and photorefractive keratectomy (PRK) in a large population. Retrospective, observational case series. Patients undergoing primary PRK or LASIK with a refractive target of emmetropia between January 1, 2008, and October 5, 2011. The Optical Express database was queried for all subjects. Data were extracted on procedure specifics, preoperative central corneal thickness (CCT), IOP (using noncontact tonometry), manifest refraction, average keratometry, age, gender, and postoperative IOP at 1 week, 1 month, and 3 months. A linear mixed methods model was used for data analysis. Change in IOP from preoperatively to 1 month postoperatively. A total of 174 666 eyes of 91 204 patients were analyzed. Hyperopic corrections experienced a smaller IOP decrease than myopic corrections for both PRK and LASIK (P<0.0001). Patients who underwent LASIK had a 0.94 mmHg (95% confidence interval [CI], 0.89-0.98) greater IOP decrease than patients who underwent PRK (P<0.0001), reflecting the effect of the lamellar flap. The decrease in IOP was linearly related to preoperative manifest spherical equivalent (MSE) for myopic PRK and LASIK (P<0.0001), weakly correlated with preoperative MSE after hyperopic LASIK, and not related to preoperative MSE after hyperopic PRK. The single greatest predictor of IOP change was preoperative IOP across all corrections. By using the available data, a model was constructed to predict postoperative IOP change at 1 month; this was able to explain 42% of the IOP change after myopic LASIK, 34% of the change after myopic PRK, 25% of the change after hyperopic LASIK, and 16% of the change after hyperopic PRK. Myopic procedures lower measured IOP more than hyperopic procedures; this decrease was proportional to the amount of refractive error corrected. Independent of the refractive correction, the creation of the lamellar LASIK flap decreased measured IOP by 0.94 mmHg. A best-fit model for IOP change was developed that may allow better interpretation of post-laser vision correction IOP values.